Preparation process of corrosion-resistant EVA foamed sheet
By using specific components and processes in EVA foam materials, the material's resilience, wear resistance and corrosion resistance are improved, the problem of insufficient mechanical properties of existing EVA foam materials is solved, and the scope of application is expanded.
Patent Information
- Application Number
- CN202510047680.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing EVA foam materials have problems such as insufficient rebound, poor wear resistance and insufficient corrosion resistance in terms of mechanical properties, which limits their application scope.
The preparation process of corrosion-resistant EVA foamed sheets is adopted, and the components include EVA, thermoplastic polyamide elastomer, ethylene propylene teremer, ethylene-octene copolymer, butyl rubber, butyl rubber, talc, zinc oxide, diapropylene peroxide, azodiformamide and glass fiber. The mechanical properties of the material are improved by blending and molding foaming technology.
It significantly improves the rebound performance, wear resistance and corrosion resistance of EVA foamed materials, expands its application environment, so that it can also show excellent softness and high elasticity in extreme environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of EVA foam materials, in particular to a preparation process of a corrosion-resistant EVA foam sheet. Background Art
[0002] EVA refers to the copolymer of ethylene-vinyl acetate, which is a random copolymer mainly formed by high-pressure bulk polymerization of ethylene (CH2=CH2) monomer and vinyl acetate (CH3 COOCH=CH2) monomer. It is also the fourth largest ethylene copolymer after HDPE, LDPE and LLDPE. Compared with the highly crystalline LDPE, EVA introduces CH3COO- side chain groups on the main chain of the molecule, which reduces the order between molecules and makes the EVA copolymer have better elasticity and lower hardness. In EVA polymers, the performance and use of copolymers change with the change of VA content on the main chain of the molecule. EVA is divided into three categories according to the change of VA content: first, VA content of 5%~40% is called EVA resin, which is also a commonly used raw material for foaming materials; second, VA content of 40%~70% is called EVA elastomer or EVA rubber; third, VA content of 70%95% is called EVA emulsion or VAE emulsion, which is often used as adhesive or coating.
[0003] Usually, EVA foam, also known as EVA sponge, is an environmentally friendly material made of EVA foam. It overcomes the shortcomings of ordinary foam rubber, such as fragility, deformation, and poor recovery, has many excellent properties, and is widely used in many fields. For example, it is used as interior decoration of vehicles and ships: such as cushion materials, heat insulation and vibration reduction materials for equipment dashboards, etc.; used in the construction field: used for roof decoration, sound insulation, waterproofing, shock absorption of foundations and walls, etc.; used in daily necessities: such as sports shoes, sports equipment, children's toys, craft gifts, stationery office, mouse pads, decorations, home furnishings, travel supplies, etc.; or used in the packaging field: as a heat-insulating, shock-proof, and moisture-proof packaging material, it is widely used in the packaging of electronic products, jewelry, hardware, cosmetics, etc.
[0004] Based on this, Chinese invention patent CN113927981B discloses a flame-retardant EVA foam that is easy to store, which includes two flame-retardant protection units and two EVA foam bodies. The two EVA foam bodies are of equal length, and the ends of the two EVA foam bodies are connected by a connecting strip. The two sides of the EVA foam body have strip convex ribs, and the strip convex ribs and the EVA foam body are integrally formed; the flame-retardant protection unit includes a flame-retardant covering layer and a strip support portion fixedly connected to the flame-retardant covering layer on both sides of the flame-retardant covering layer, and the inner side of the strip support portion has two limit strips, and a strip slot that cooperates with the strip convex ribs is formed between the two limit strips. The EVA foam disclosed in this invention can effectively retard and is easy to store.
[0005] However, the EVA foam disclosed above still has technical problems such as insufficient mechanical properties such as rebound. Specifically, the flame-retardant EVA foam disclosed above is mainly achieved by setting a flame-retardant protection unit on the foam body, and making the flame-retardant protection unit realize the flame-retardant function. However, in the non-covered area of the flame-retardant protection unit, the material itself still does not have the ability to flame retard; moreover, the separate setting of the flame-retardant material will also affect the environmental performance of the material; and it cannot improve the mechanical properties such as the rebound performance, wear resistance and corrosion resistance of the foam material itself. Generally speaking, in order to make the foam material have excellent wear resistance, good antistatic, UV resistance, high strength, excellent heat resistance and other comprehensive properties and low production cost, it is necessary to add an appropriate amount of inorganic filler to the foam material. Further, rubber elastic materials are usually used as modified matrix materials of EVA foam materials to complement their performance because of their excellent softness, excellent elasticity, good mechanical properties and other advantages. Therefore, how to further improve the wear resistance, flame retardancy and elasticity of EVA foam while ensuring the environmental performance of EVA foam materials requires improving the EVA foam materials themselves. Summary of the invention
[0006] Based on this, it is necessary to provide a preparation process of a corrosion-resistant EVA foam sheet in order to solve the technical problem of how to improve the mechanical properties of the EVA foam material.
[0007] A preparation process of a corrosion-resistant EVA foam sheet. The components thereof include, by weight: 55-65 parts of EVA, 5-15 parts of thermoplastic polyamide elastomer, 10-25 parts of ethylene propylene diene rubber, 0-15 parts of ethylene-octene copolymer, 0-8 parts of butadiene rubber, 0-8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 7.5-15 parts of glass fiber.
[0008] Specifically, in an embodiment of a preparation process of a corrosion-resistant EVA foam sheet, the components include, by mass: 65 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 10 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0009] Specifically, in an embodiment of another preparation process of a corrosion-resistant EVA foam sheet, the components, by mass, include: 60 parts of EVA, 7.5 parts of thermoplastic polyamide elastomer, 12.5 parts of ethylene propylene rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0010] Specifically, in an embodiment of a preparation process of another corrosion-resistant EVA foam sheet, the components include, by mass: 55 parts of EVA, 15 parts of thermoplastic polyamide elastomer, 25 parts of EPDM rubber, 15 parts of ethylene-octene copolymer, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 7.5 parts of glass fiber.
[0011] Specifically, in an embodiment of a preparation process of another corrosion-resistant EVA foam sheet, the components include, by mass: 55 parts of EVA, 10 parts of thermoplastic polyamide elastomer, 15 parts of EPDM rubber, 8 parts of butadiene rubber, 8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropyl peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0012] Specifically, in an embodiment of a preparation process of another corrosion-resistant EVA foam sheet, the components, by mass, include: 55 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 20 parts of EPDM rubber, 10 parts of ethylene-octene copolymer, 5 parts of butadiene rubber, 5 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropyl peroxide, 3 parts of azodicarbonamide and 10 parts of glass fiber.
[0013] Specifically, in another embodiment of the preparation process of the corrosion-resistant EVA foam sheet, edge felt glass fiber is used instead of glass fiber, and the input amount of the edge felt glass fiber is 8 parts by mass.
[0014] Specifically, in another embodiment of the preparation process of the corrosion-resistant EVA foam sheet, filament glass fiber is used instead of glass fiber, and the input amount of the filament glass fiber is 5 parts by mass.
[0015] In summary, the preparation process of a corrosion-resistant EVA foam sheet of the present invention proposes a foam ratio with both hardness and resilience, and its components include, by mass, 55-65 parts of EVA, 5-15 parts of thermoplastic polyamide elastomer, 10-25 parts of ethylene propylene diene rubber, 0-15 parts of ethylene-octene copolymer, 0-8 parts of butadiene rubber, 0-8 parts of butyl rubber, 8 parts of talcum powder, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 7.5-15 parts of glass fiber. In practical applications, in more extreme environments such as cold use environments, EVA foam materials have the disadvantages of high hardness and poor elasticity; on the other hand, even at room temperature, EVA foam materials also have the problem of easy wear, which greatly limits their scope of application. The present invention discloses an EVA foam material with excellent softness, high elasticity, high wear resistance and corrosion resistance to expand the application environment of EVA foam materials. Therefore, the preparation process of the corrosion-resistant EVA foam sheet of the present invention solves the technical problem of how to improve the resilience performance of the EVA foam material. DETAILED DESCRIPTION
[0016] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0017] Generally speaking, the main raw materials of the molding formula of foaming materials include: foaming agent, cross-linking agent, inorganic filler, etc. These ingredients have an important influence on the elasticity, density, foaming ratio and mechanical properties of the foaming material.
[0018] For example, as the percentage of the blowing agent azodicarbonamide increases, the density of the foamed product decreases, the color deepens, and in severe cases, large pores appear inside the material, and the material turns yellow, affecting the color matching and causing problems in adjusting the products to white or light colors. If the amount of azodicarbonamide is small, the foamed material will have defects such as a small number of bubbles and insufficient foaming ratio, which will not meet the requirements for use.
[0019] In addition, for the cross-linking agent diisopropylbenzene peroxide, when its dosage is insufficient, the material will show obvious sticking to the mold, softening and other phenomena, resulting in foaming failure; and when its dosage is too large, the foaming material will become brittle and the surface will crack, resulting in defects such as the foaming product cannot be used.
[0020] Furthermore, when the addition amount of the inorganic filler zinc oxide slowly increases, the density, strength and toughness of the foamed material decrease accordingly; the reason is that when the amount of zinc oxide used is small, the decomposition temperature of the foaming agent azodicarbonamide is still at a high level, causing its decomposition rate to be much lower than the cross-linking speed of the cross-linking agent diisopropyl peroxide. At this time, the material shows a more obvious insufficient foaming ratio, increased product density and increased hardness; and when the amount of zinc oxide used is large, the decomposition temperature of the foaming agent azodicarbonamide is greatly reduced, causing its decomposition rate to be much higher than the cross-linking speed of the cross-linking agent diisopropyl peroxide. The foaming ratio of the material is relatively large, the product density decreases, the hardness decreases, and obvious insufficient cross-linking occurs.
[0021] For example, after adding ultrafine calcium carbonate, the density and hardness of the foamed material increase, the elongation at break decreases, and the strength increases. Therefore, calcium carbonate has a certain reinforcement effect, and as its content increases, the reinforcement gradually disappears, which is manifested as the material becomes harder and the density increases; as the calcium carbonate content increases, the strength and toughness of the composite foamed material first increase and then decrease; calcium carbonate has a certain reinforcement and heat stability for cross-linked foamed materials. When the amount of calcium carbonate increases, the hardness and density of the foamed material increase, and the heat stability will also increase accordingly.
[0022] In summary, the molding formula of the foaming material has an essential and guiding influence on the performance of the final foam product. Moreover, different contents of the same component will also have a key impact on the final performance of the foam product.
[0023] Based on this, the invention discloses a preparation process of a corrosion-resistant EVA foam sheet, wherein the components thereof include, by weight: 55-65 parts of EVA, 5-15 parts of a thermoplastic polyamide elastomer, 10-25 parts of ethylene propylene diene rubber, 0-15 parts of an ethylene-octene copolymer, 0-8 parts of butadiene rubber, 0-8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 7.5-15 parts of glass fiber.
[0024] Specifically, EPDM has the characteristics of good weather resistance, high elasticity, excellent flexibility, corrosion resistance, etc. Its Tg is low, and it still has good elasticity and flexibility even at low temperatures. The low temperature resistance of EVA composite foam materials can be improved by blending EPDM in the basic formula of EVA foam. For example, existing comparative experiments can show that the addition of EPDM can significantly reduce the hardness of the foam material and improve the elasticity. Compared with before the addition of EPDM, the elasticity of the foam is increased from 4% to 26%; before and after the addition of EPDM, the density and foaming ratio of the foam material change little, which can be basically ignored compared with the hardness and elasticity. Considering the various properties of the foam material at low temperature, the hardness of the foam material is reduced by 40% at most and the elasticity is increased by 5 to 6 times at most after the addition of the elastomer EPDM. On the whole, when the input amount of EPDM is 10 to 25 parts, it can have a more favorable effect on the elasticity and toughness of the EVA foam material.
[0025] Further, ethylene-octene copolymer will affect the hardness and elasticity of EVA foamed material. That is, as the content of ethylene-octene copolymer increases, the hardness of the foamed material decreases and the elasticity increases; and when the content of ethylene-octene copolymer is greater than 15 parts, the hardness and elasticity of the material gradually tend to be flat with the change of the content of ethylene-octene copolymer. Therefore, the introduction of ethylene-octene copolymer can change the melt strength and adhesion of EVA. When a small amount of ethylene-octene copolymer is added, the melt fluidity of EVA changes less, and the adhesion of EVA affects the dispersion degree of the foaming agent powder; and when the amount of ethylene-octene copolymer added reaches a certain value, the adhesion of EVA increases, and the melt strength is improved to a certain extent, which is conducive to preventing gas from escaping from the melt, thereby affecting the hardness and elasticity of the foamed product. Comprehensively speaking, ethylene-octene copolymer can be added without addition, or up to 8 parts can be added.
[0026] Furthermore, butadiene rubber has a lower Tg, good cold resistance, higher elasticity and flexibility; after adding butadiene rubber to EVA foam material, the hardness of EVA foam material at low temperature can be reduced, and its elasticity at low temperature can be enhanced. Similarly, butyl rubber can also play a similar role; before and after the addition of butyl rubber, the density and foaming ratio of EVA foam material change little; but it can also improve the low temperature performance of EVA foam material. On the whole, butadiene rubber or butyl rubber can be added without addition, or can be added up to 15 parts. Specifically, the addition of talcum powder can improve the hardness, elasticity, wear resistance and corrosion resistance of EVA foam products. When the amount of talcum powder added increases, the hardness of the EVA foam material increases and the elasticity decreases. The increase in the talcum powder content reduces the proportion of the elastic matrix material, and also reduces the fluidity and adhesion of the EVA melt, and reduces the uniformity of foaming dispersion, thereby increasing the hardness of the foamed product and reducing the elasticity; on the other hand, while talcum powder supplements the stability of the product, it also has a certain improvement effect on the tearing performance and elongation at break of the product. Overall, the optimal addition amount of talcum powder is 8 parts.
[0027] Furthermore, zinc oxide is used as a foaming aid for azodicarbonamide in a relatively small amount. However, the addition of zinc oxide can regulate the decomposition rate of azodicarbonamide to be consistent with the crosslinking rate of diisopropylbenzene peroxide, thereby affecting the softness and elasticity of the foamed product; on the other hand, the addition of more zinc oxide not only acts as a foaming aid, but also acts as a filler, reducing the shrinkage stability of the foamed product. Considering the production cost, when the zinc oxide content is selected as 2 parts in the optimal ratio, the foamed material has a lower hardness and a higher elasticity; and the final foamed product can also take into account the wear-resistant performance.
[0028] Further, several specific embodiments of the preparation process of a corrosion-resistant EVA foam sheet of the present invention are as follows, by weight: Example 1: 65 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 10 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0029] Example 2: 60 parts of EVA, 7.5 parts of thermoplastic polyamide elastomer, 12.5 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0030] Example 3: 55 parts of EVA, 15 parts of thermoplastic polyamide elastomer, 25 parts of EPDM rubber, 15 parts of ethylene-octene copolymer, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 7.5 parts of glass fiber.
[0031] Example 4: 55 parts of EVA, 10 parts of thermoplastic polyamide elastomer, 15 parts of EPDM rubber, 8 parts of butadiene rubber, 8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
[0032] Example 5: 55 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 20 parts of EPDM rubber, 10 parts of ethylene-octene copolymer, 5 parts of butadiene rubber, 5 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 10 parts of glass fiber.
[0033] Furthermore, the aforementioned glass fiber can be ordinary glass fiber, for example, 3B glass fiber; it can also be replaced in equal proportion with seam felt glass fiber or long glass fiber filament. Specifically, the seam felt glass fiber can form a continuous fiber network with good tensile strength and impact resistance; the opening of the felt can make the foaming material more permeable, which is conducive to the improvement of strength: the price is relatively low and the cost is more competitive; but it only has unidirectional performance and cannot provide strength in all directions at the same time. In addition, long glass fiber filaments have high tensile strength and bending strength; have high hardness and cutting properties, but have the disadvantage of greater wear on processing equipment. Ordinary glass fiber has the advantages of good fiber quality, excellent strength and modulus; it can provide multi-directional strength and is suitable for the requirements of multi-directional mechanical properties; the surface is smooth and easy to paint and surface treat. More specifically, when using seam felt glass fiber, its input amount is 8 parts; when using filament glass fiber, its usage amount is 5 parts.
[0034] Furthermore, in the manufacturing process of the preparation process of a corrosion-resistant EVA foam sheet of the present invention, the specific manufacturing process includes the following steps: S1: plasticizing the rubber material, for example, setting the temperature of the open mill to 50°C, the roller distance to 2mm, and the speed to 25r / min; adding EPDM rubber, butadiene rubber or butyl rubber according to a preset ratio for open mixing and plasticizing, and leaving it for 2 hours for use; S2: Mixing and molding; setting the temperature of the open mill to 60°C and the roller distance to 0.5mm; first, adding EVA raw materials according to a preset ratio to the double-roll open mill for mixing, after rolling, thinning through 6 times, and triangular wrapping 3 times; then, adding the plasticized rubber material in step S1, and then adding thermoplastic polyamide elastomer, talcum powder, zinc oxide, diisopropylbenzene peroxide and azodicarbonamide according to a preset ratio and mixing; after rolling, adjusting the roller distance to 2mm, thinning through 6 times again, and triangular wrapping 3 times to obtain a blended composite material; S3: Compression molding and foaming: first, heat the mold of the flat vulcanizer to not less than 60°C, and then put the glass fiber of the preset ratio into the mold; then set the upper and lower plates of the flat vulcanizer to 185°C, the pressure to 7.5MPa, and the time to 400s; and spray the blended composite material obtained in step S2 from the mixing head, so that the composite material is compression molded and foamed on the flat vulcanizer, and finally obtain an EVA foamed product; S4: Finally, the obtained EVA foamed product is placed at room temperature for 24-36 hours and then cut and manufactured according to the requirements.
[0035] Specifically, the EVA composite foam material prepared by compression foaming in the above-mentioned embodiments can be subjected to a rebound rate test, and the rebound rate test is carried out in accordance with the provisions of GB / T1681-2009, and each sample is randomly measured 3 times, and the average value is used as the final rebound data of the sample. The test standard of the hardness test of each embodiment and comparative example is carried out in accordance with ASTM / D297-93, and a Shore A hardness tester is used to directly test the sample surface, and each sample is randomly measured 3 times, and the average value is used as the final hardness of the sample.
[0036] Specifically, in the experiment, Comparative Example 1 is: 65 parts of EVA, 15 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide and 3 parts of azodicarbonamide.
[0037] Table 1: Hardness and resilience test data of various embodiments and comparative examples
[0038] It can be seen that the preparation process of the corrosion-resistant EVA foam sheet of the present invention can improve the hardness and resilience of the EVA foam product while ensuring the environmental performance of the material itself; so that the EVA foam material can further improve the elasticity of the material under the premise of improving the wear resistance and corrosion resistance.
[0039] In summary, the preparation process of a corrosion-resistant EVA foam sheet of the present invention proposes a foam ratio with both hardness and resilience, and its components include, by mass, 55-65 parts of EVA, 5-15 parts of thermoplastic polyamide elastomer, 10-25 parts of ethylene propylene diene rubber, 0-15 parts of ethylene-octene copolymer, 0-8 parts of butadiene rubber, 0-8 parts of butyl rubber, 8 parts of talcum powder, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 7.5-15 parts of glass fiber. In practical applications, in more extreme environments such as cold use environments, EVA foam materials have the disadvantages of high hardness and poor elasticity; on the other hand, even at room temperature, EVA foam materials also have the problem of easy wear, which greatly limits their scope of application. The present invention discloses an EVA foam material with excellent softness, high elasticity, high wear resistance and high corrosion resistance to expand the application environment of EVA foam materials. Therefore, the preparation process of the corrosion-resistant EVA foam sheet of the present invention solves the technical problem of how to improve the resilience performance of the EVA foam material.
[0040] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0041] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A preparation process of a corrosion-resistant EVA foam sheet, characterized in that: The components include, by mass, 55-65 parts of EVA, 5-15 parts of thermoplastic polyamide elastomer, 10-25 parts of EPDM rubber, 0-15 parts of ethylene-octene copolymer, 0-8 parts of butadiene rubber, 0-8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 7.5-15 parts of glass fiber.
2. The preparation process of a corrosion-resistant EVA foam sheet according to claim 1, characterized in that: The components include, by mass: 65 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 10 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
3. The preparation process of a corrosion-resistant EVA foam sheet according to claim 1, characterized in that: The components include, by mass: 60 parts of EVA, 7.5 parts of thermoplastic polyamide elastomer, 12.5 parts of EPDM rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
4. The preparation process of a corrosion-resistant EVA foam sheet according to claim 1, characterized in that: The components include, by mass, 55 parts of EVA, 15 parts of thermoplastic polyamide elastomer, 25 parts of EPDM rubber, 15 parts of ethylene-octene copolymer, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of dicumyl peroxide, 3 parts of azodicarbonamide and 7.5 parts of glass fiber.
5. The preparation process of a corrosion-resistant EVA foam sheet according to claim 1, characterized in that: The components include, by mass: 55 parts of EVA, 10 parts of thermoplastic polyamide elastomer, 15 parts of EPDM rubber, 8 parts of butadiene rubber, 8 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 15 parts of glass fiber.
6. The preparation process of a corrosion-resistant EVA foam sheet according to claim 1, characterized in that: The components include, by mass, 55 parts of EVA, 5 parts of thermoplastic polyamide elastomer, 20 parts of EPDM rubber, 10 parts of ethylene-octene copolymer, 5 parts of butadiene rubber, 5 parts of butyl rubber, 8 parts of talc, 2 parts of zinc oxide, 0.8 parts of diisopropylbenzene peroxide, 3 parts of azodicarbonamide and 10 parts of glass fiber.
7. A process for preparing a corrosion-resistant EVA foam sheet according to any one of claims 1 to 6, characterized in that: Edge felt glass fiber is used to replace glass fiber, and the input amount of edge felt glass fiber is 8 parts by mass.
8. A process for preparing a corrosion-resistant EVA foam sheet according to any one of claims 1 to 6, characterized in that: Filament glass fiber is used to replace glass fiber, and the input amount of filament glass fiber is 5 parts by weight.
Citation Information
Patent Citations
A flame-retardant EVA foam that is easy to store
CN113927981B